1423 Quality and Efficacy of Multidisciplinary Team (MDT) Discussion Quality Assessment Tools and Checklists: A Systematic Review. (12th October 2021) - Brown, G; Young, A; Rymell, R
Abstract: Aim: MDT discussion is the gold standard for cancer care in the UK. With the cancer incidence and complexity of treatments both increasing, demand for MDT discussion is growing. The need for efficiency, whilst maintaining high standards, is therefore clear. Paper-based MDT quality assessment tools and discussion checklists may represent a practical method of monitoring and improving MDT practice. This review aims to describe and appraise these tools, as well as consider their value to quality improvement. Method: MEDLINE, Embase and PsycInfo were searched using pre-defined terms. PRISMA methodology was followed throughout. Studies were included if they described the development of a relevant tool/checklist, or if an element of the methodology further informed tool quality assessment. To investigate efficacy, studies using a tool as a method of quality improvement in MDT practice were also included. Study quality was appraised using the COSMIN risk of bias checklist or the Newcastle-Ottawa scale, depending on study type. Results: The search returned 6888 results. 17 studies were included, and 6 different tools were identified. Overall, methodological quality in tool development was adequate to very good for assessed aspects of validity and reliability. Clinician feedback was positive. In one study, the introduction of a discussion checklist improved MDT ability to reach a decision from 82.2% to 92.7%. Improvement was also noted in the quality of information presented and the quality of teamwork. Conclusions: Several tools for assessing and guiding MDT discussions are available. Although limited, current evidence indicates sufficient rigour in their development and their potential for quality improvement.